COPD in Non-smoker Women with Biomass Fuel Exposure (Chulha) - A review Article - R Gaikwad, Dr. Deepali (International Journal of Innovative Research in Medical Science, 2017)
Exposure to indoor air pollution due to incomplete combustion of biomass fuel remains significant risk factor for chronic bronchitis and chronic obstructive pulmonary disease (COPD). In developing countries like India, especially in rural areas combustion of biomass fuel is the most important source of air pollution. This article aims to increase awareness regarding biomass exposure and respiratory morbidity in women.